Psychological stress and job satisfaction in middle management executives: a test of job demand control support model - Singh P.; Bhardwaj P.; Sharma S.K.; Agrawal A.K. (My University, 2025)
Occupational stress is one of the most critical factors related to the employees’ well-being in any organisation. Employees working in managerial positions are more prone to work-related stress because of the nature of the job and the responsibilities associated with the position. Job demands, control and support at the workplace are vital factors that affect stress and job satisfaction in employees. This research aims to study if the job demand control support model can explain psychological stress and job satisfaction. Two hundred ten middle management executives of an Indian public telecom organisation participated in the study. ANOVA is used for the data analysis. The study results reported no difference in psychological stress of employees in different job categories as defined by the job demand control support model. Job control and support have a significant effect on job satisfaction. There was no significant interaction effect on either psychological stress or job satisfaction. Copyright © 2022 Inderscience Enterprises Ltd.